Acquaintance, attitude, and perceived barriers regarding scientific research publications among clinical nurses: a cross-sectional study at tertiary care hospitals in western Rajasthan - Kalal, Nipin; Vel, N. sabari; Chaudhary, Saroj; Meena, Savita; Meena, Sonam; Bhichar, Sonu; Singh, Spraha (Frontiers in Research Metrics and Analytics, 2024)
Introduction In today's era, conducting nursing research is crucial for the advancement of the nursing profession. Scientific publications in clinical research aim to improve patient care outcomes and foster a sense of importance for nurses within the healthcare team. However, clinical nurses often fall behind due to factors such as limited familiarity, attitudes toward research, and encountered barriers. Objectives This study was conducted to assess the knowledge, attitude, and perceived barriers regarding scientific research publications among clinical nurses at tertiary care hospitals in western Rajasthan. Methodology A cross-sectional descriptive study was conducted among the clinical nurses. The participants were assessed for their knowledge, attitude, and perceived barriers regarding scientific research publications through a self-administered questionnaire. Results The study revealed that 92% of the participants lacked sufficient knowledge about scientific research publications and 78.3% experienced moderate perceived barriers. Pearson's correlation coefficient indicated a weak positive correlation (r = 0.143, p = 0.007) between knowledge and attitude and a significant negative correlation (r = −0.143, p = 0.012) between knowledge and perceived barriers. However, multiple linear regression analysis showed no significant relationship among the clinical nurses in terms of knowledge, attitude, and perceived barriers toward scientific research publications. Conclusion This study on clinical nurses revealed that the majority had insufficient knowledge about scientific research, while over half had neutral attitudes toward research publications. In addition, a significant portion of the clinical nurses reported experiencing moderate perceived barriers.